Design of an artificial transcriptional system for production of high levels of recombinant proteins in tobacco (Nicotiana benthamiana) - Yun, Areum; Kang, Joohyun; Lee, Juhun; Song, Shi-Jian; Hwang, Inhwan (Frontiers in Plant Science, 2023)
Plants have recently received much attention as a means of producing recombinant proteins because they are easy to grow at a low cost and at a large scale. Although many plant protein expression systems have been developed, there remains a need for improved systems that deliver high yields of recombinant proteins. Transcription of the recombinant gene is a key step in increasing the yield of recombinant proteins. However, revealed strong promoters, terminators, and transcription factors that have been identified do not necessarily lead to high level production of recombinant proteins. Thus, in this study, a strong expression system was designed to produce high levels of recombinant protein consisting of a novel hybrid promoter, FMʹM-UD, coupled with an artificial terminator, 3PRt. FMʹM-UD contained fragments from three viral promoters (the promoters of Mirabilis mosaic caulimovirus (MMV) full-length transcript, the MMV subgenomic transcript, and figwort mosaic virus subgenomic transcript) and two types of cis-acting elements (four GAL4 binding sites and two zinc finger binding sites). The artificial terminator, 3PRt, consisted of the PINII and 35S terminators plus RB7, a matrix attachment region. The FMʹM-UD promoter increased protein levels of reporters GFP, RBD:SD1 (part of S protein from SARS-CoV-2), and human interleukin-6 (hIL6) by 4–6-fold, 2-fold, and 6-fold, respectively, relative to those of the same reporters driven by the CaMV 35S promoter. Furthermore, when the FMʹM-UD/3PRt expression cassette was expressed together with GAL4/TAC3d2, an artificial transcription factor that bound the GAL4 binding sites in FMʹM-UD, levels of hIL6 increased by 10.7-fold, relative to those obtained from the CaMV 35S promoter plus the RD29B terminator. Thus, this novel expression system led to the production of a large amount of recombinant protein in plants.